Numerical and experimental results of liquid slosh in a partially filled cylindrical tank - Hussain Shah, Qasim; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
Several experiments with different water levels were conducted to monitor the effect of water slosh in the container tank. This experimental study on fluid slosh was conducted to validate the results of the numerical models. The observation of the experimental results shows that strain gage-1 experienced compression strain at the top of the tank, while strain gage-2 experienced tension strain at the frontal area. The unit of the strain is displayed in pdm. From this experiment, the values for strain gage-1 is quite lower than strain gage-2.This big different is due to strain gage-2 in the frontal area is experience more forces and moments compared to the strain gage- 1 at the top of the tank.